2015
DOI: 10.1091/mbc.e14-07-1194
|View full text |Cite
|
Sign up to set email alerts
|

HIF-dependent regulation of claudin-1 is central to intestinal epithelial tight junction integrity

Abstract: This study demonstrates a critical link between hypoxia-inducible factor (HIF) and claudin-1 (CLDN1). HIF1β-deficient intestinal epithelial cells develop abnormal tight junction (TJ) structure and have striking barrier defects. CLDN1 is an HIF target gene, and overexpression of CLDN1 in HIF1β-deficient cells restores TJ structure and function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
125
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 174 publications
(147 citation statements)
references
References 43 publications
(67 reference statements)
9
125
1
2
Order By: Relevance
“…The NC group had a somewhat higher expression of macrophage migration inhibitory factor, serpin, and interleukin 8; however, these differences were not statistically significant (Figure 3C and 3D). Another miR‐155 target hypoxia‐inducible factor 1α, the mediator of cellular response to hypoxia and regulator of TJ integrity,25, 26 was undetectable in the cell lysates from all analyzed cell groups (neither by ELISA nor Western blot, data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…The NC group had a somewhat higher expression of macrophage migration inhibitory factor, serpin, and interleukin 8; however, these differences were not statistically significant (Figure 3C and 3D). Another miR‐155 target hypoxia‐inducible factor 1α, the mediator of cellular response to hypoxia and regulator of TJ integrity,25, 26 was undetectable in the cell lysates from all analyzed cell groups (neither by ELISA nor Western blot, data not shown).…”
Section: Resultsmentioning
confidence: 93%
“…Moreover, in vivo analysis revealed the importance of HIF-mediated CLDN1 expression during experimental colitis. These results identify a critical link between HIF and specific TJ function, providing important insight into mechanisms of HIF-regulated epithelial homeostasis (13).…”
Section: Molecular Aspects Of Barrier Regulation In the Mucosamentioning
confidence: 81%
“…Claudin-1 (CLDN1) is an important "tight" claudin and has been shown to be dysregulated in a variety of human diseases, including IBD (40). In a recent screen of TJ targets, CLDN1 was identified as a central mediator of aberrant junctional morphology in HIF-1β-deficient intestinal epithelial cell (IEC) lines (13). Using both loss-and gain-of-function approaches, this work showed that HIF maintains CLDN1 expression through binding hypoxia response element (HRE) sequences in the gene promoter.…”
Section: Molecular Aspects Of Barrier Regulation In the Mucosamentioning
confidence: 99%
“…To this end, we exposed Caco-2 and T84 cells to butyrate and profiled the expression of a panel of junctional proteins known to be important in barrier function: Cldn1, Cldn2, Cldn3, Cldn7, occludin, E-cadherin, JAM-A and ZO-1 (30). We have used this approach successfully in the past to define targets for barrier regulation by hypoxia-inducible factor (31). Our studies revealed that butyrate preferentially repressed the expression of Cldn2 relative to control in both Caco2 (0.22 ± 0.14) and T84 cells (0.08 ± 0.07) (Figure 5A and B, p<0.001).…”
Section: Resultsmentioning
confidence: 99%